(untitled) (AIUB Journal of Science and Engineering (AJSE), 2024)
In the context of earthquake and flood disasters, effective communication remains a pivotal concern due to the vulnerability of conventional networks. This study presents a comparative analysis of off-grid communication technologies—namely WiFi and LoRa—with the aim of ascertaining their efficacy in addressing this challenge and proposes a LoRa rescue model. Critical parameters such as communication range, SNR (Signal to noise ratio), RSSI (Received Signal Strength Indicator) rate, data transmission speed, bandwidth, frequency, and reliability are evaluated. The outcomes of this investigation highlight the importance of alternative communication solutions when centralized networks falter. Particularly, the intrinsic attributes of LoRa exhibit potential for sustaining connectivity amidst network disruptions. These findings not only enrich the discourse on disaster management strategies but also offer insights into crafting adaptive and resilient communication systems. Informed decision-making regarding communication technology deployment in emergency contexts in order to make the rescue process convenient and reliable is the direct implication of this research.